2017
DOI: 10.1007/s10043-017-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the approximations of light propagation on quantitative photoacoustic tomography using two-dimensional photon diffusion equation and linearization

Abstract: Quantitative photoacoustic tomography (QPAT) employing a light propagation model will play an important role in medical diagnoses by quantifying the concentration of hemoglobin or a contrast agent. However, QPAT by the light propagation model with the three-dimensional (3D) radiative transfer equation (RTE) requires a huge computational load in the iterative forward calculations involved in the updating process to reconstruct the absorption coefficient. The approximations of the light propagation improve the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…To overcome the limitations of the DE, the Radiative Transfer Equation (RTE) has been addressed as a rigorous model for light transport in biological tissues and has become a focus of investigations in QPAT [15][16][17][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Superscripts 1 Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome the limitations of the DE, the Radiative Transfer Equation (RTE) has been addressed as a rigorous model for light transport in biological tissues and has become a focus of investigations in QPAT [15][16][17][22][23][24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Superscripts 1 Introductionmentioning
confidence: 99%
“…Consequently, the anisotropy factor can provide an additional intrinsic contrast for optical imaging. To overcome the limitations of the DE, the Radiative Transfer equation (RTE) has been addressed as a rigorous model for light transport in biological tissues and has become a focus of investigations in QPAT [15][16][17][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. In the optical inverse problem of QPAT, it has been shown that the absorption coefficient μ a can be reconstruct if one light source is used whereas the simultaneous reconstruction of (μ a , μ s ) needs multiple optical illuminations, so-called multisource QPAT [16,25,36,37].…”
Section: Introductionmentioning
confidence: 99%